Empowering the Children of Asnaf Komuniti Sungai Nibong through the Ablution and Prayer Seminar Program as Representation of Strengthening Islamic Faith - Mangda Tyas Husnawati; Khusniati Rofiah (International Journal of Community Engagement Payungi, 2024)
The article aims to empower the Children of Asnaf Komuniti Sungai Nibong through the Ablution and Prayer Seminar Program as a Representation of Strengthening the Islamic Faith in Improving the Quality of Life. As a representation of the strengthening of the Islamic faith, the International Community Service Program in 2024 participants want to contribute to providing an education and learning platform to the community around the place of service, or more precisely, to children who do not yet have emotional maturity so that they are very vulnerable to being carried away by negative things due to globalization. Therefore, in this case, the International Community Service Program in 2024 participants will hold an Ablution and Prayer Seminar Program as a forum to re-strengthen the Islamic faith of children in Pulau Pinang, Malaysia. The Ablution and Prayer Seminar Program was held at Pangsapuri Wakaf Siti and Hajjah Norijah with the children of Asnaf Kominiti Sungai Nibong. The Ablution and Prayer Seminar itself is one of the flagship work programs of the International Community Service Program in 2024 participants as an effort to empower children as well as a form of community service which is expected to be helpful and have a positive impact on the residents of Pulau Pinang Malaysia, especially for the children of Asnaf Kominiti Sungai Nibong. The Asset Based Community Development (ABCD) approach is used with Participatory and Collaborative service implementation methods. The result of community service through the holding of the Ablution and Prayer Seminar Program is that it can further improve the quality of life for children of Asnaf Komuniti Sungai Nibong in Pangsapuri Wakaf Siti and Hajjah Norijah Pulau Pinang, Malaysia.